DESIGN AND DEVELOPMENT OF A 3-AXIS VERTICAL MILLING MACHINE CONTROL LOGIC ARCHITECTURE USING IEC 61499 FUNCTION BLOCK - Othman, M.A.; Jamaludin, Z.; Minhat, M.; Patwari, M.A.U. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
The inflexibility of CNC control structure and the use of outdated CNC data interface are two major issues that limit the growth of CNC system. Emergence of STEP-NC standard provides comprehensive and rich information up to controller level that bring opportunity to overcome these problems. However, STEP-NC is only a passive data interface without intelligent functionality thus an IEC 61499 function block standard has been chosen as the research strategy to provide intelligent functionality to the proposed system. This then simultaneously resolves the inflexibility of the CNC control structure using distributed and layered architecture approach. This paper presents development of control logic motion system for a 3-axis vertical milling machines based on the IEC 61499 function block (FB). For control of the cutting processes, two types of motion control subsystems which are primary and feed motions are developed. Results showed that the designed FB is capable to provide the required functionality and represent actual machining working states. In future, this subsystem will be automatically forwarded with machining parameters and tool-paths data generation using native data generation module for performing actual cutting processes.